Citizenship education and pedagogical practices of the teacher of the 1st cycle of basic education - Costa, Ana Sofia (2021)
Citizenship Education is being increasingly debated, due to social changes that are rapidly occurring. Nowadays, the school must take on new challenges that should be reflected in teachers’ pedagogical practices. This is where school gains prominence as a main agent in the formation of active citizens, capable of contributing to the development and well-being of the society in which they live, by educating them for citizenship. Therefore, the present investigation aimed to understand if Citizenship Education is a disciplinary area valued by teachers in the 1st Cycle of Basic Education (CEB) [years 1-4] in the classroom, based in their perspectives. For this, we tried to verify how often Citizenship Education is addressed, in the classroom; to know the importance attributed to this subject in the various areas of student training; to identify those responsible for selecting the content covered in Citizenship Education; and to analyse the thematic areas of Citizenship Education more and less worked on in the classroom. To this end, we carried out a descriptive research using a questionnaire sent to a non-probabilistic sample of ninety-one 1st CEB teachers working in the municipality of Viseu (Portugal). The data showed that teachers attribute relevance to Citizenship Education teaching in various areas of educational action, and approach it quite frequently in their teaching practice. It was also observed that content selection responsibility rests mainly over teachers and students, and that there are thematic areas of Citizenship little addressed, such as the European Dimension of Education, or the of Education for Entrepreneurship. Considering that school is a privileged space for citizenship development, it is required that teachers guide their pedagogical practices towards themes on which it is necessary to reflect, in order to promote the development of social skills from a very early age.